JASA PENYEDIA EKOSISTEM TERUMBU KARANG DI KAWASAN SUAKA ALAM PERAIRAN KEPULAUAN RAJA AMPAT DARI PERSPEKTIF VALUASI EKONOMI - Muhammad Nur Arkham; Yudi Wahyudin; Muhammad Reza Pahlevi; Roma Yuli F. Hutapea (Jurnal Kelautan, 2020)
ABSTRACTThe existence of coral reef ecosystems in the SAP area of Raja Ampat Regency and surrounding seas has to provisioning services is used from the local fisherman as a source of livelihood. The purpose of this study is to estimate the economic value of the services of providers of capture fisheries to coral reef ecosystems in the SAP area of Raja Ampat Islands with the effect on production (EOP) approach. Data needed in this study are primary and secondary data. Analysis of the data used is the description analysis and economic valuations carried out by assuming a consumer surplus (CS) of resources. The results of the study showed that based on fishermen's perceptions of 59% the existence of coral reef ecosystems in the SAP Area of Raja Ampat Regency and surrounding seas provide a service in the form of productivity of fish catches associated with coral reefs. Based on the Effect on Production (EOP) analysis approach, it is estimated that the economic value of the consumer surplus (CS) of the coral reef ecosystem is IDR. 442,647,305.00 / person / year with an area of 2178.7 hectares and the number of beneficiary fishermen of 238 people, the total economic value per resource is IDR. 48,354,550.00 / Ha / Person / Year.Keywords: economic valuation, provisioning services, capture fisheries, consumer surplus, coral reef ecosystem, Raja Ampat RegencyABSTRAKKeberadaan ekosistem terumbu karang di Kawasan SAP Kabupaten Raja Ampat dan laut sekitarnya memberikan sebuah jasa penyediaan perikanan yang dimanfaatkan oleh nelayan sekitar sebagai sumber penghidupan. Tujuan dari penelitian ini adalah mengestimasi nilai ekonomi jasa penyedia perikanan tangkap ekosistem terumbu karang di Kawasan SAP Kepulauan Raja Ampat dengan pendekatan effect on production (EOP). Data yang dibutuhkan dalam penelitian adalah data primer dan sekunder. Analisis data menggunakan analisis deskriptif dan valuasi ekonomi dilakukan dengan menduga surplus konsumen (CS) sumberdaya. Hasil dari penelitian menunjukkan bahwa berdasarkan persepsi nelayan sebesar 59% keberadaan ekosistem terumbu karang di Kawasan SAP Kabupaten Raja Ampat dan laut sekitarnya memberikan jasa penyediaan berupa produktivitas hasil tangkapan ikan yang berasosiasi dengan terumbu karang. Berdasarkan pendekatan analisis Effect on Production (EOP) didapatkan estimasi nilai ekonomi dari surplus konsumen (CS) terhadap ekosistem terumbu karang sebesar Rp. 442.647.305,00/Orang/Tahun dengan luas kawasan 2178,7 Ha dan jumlah nelayan pemanfaat sebanyak 238 orang didapatkan nilai ekonomi total per sumberdaya yaitu sebesar Rp. 48.354.550,00/Ha/Orang/Tahun. Kata kunci: valuasi ekonomi, jasa penyediaan, perikanan tangkap, surplus konsumen, ekosistem terumbu karang, Kabupaten Raja Ampat